Ranking user generated content using topic models - Ma, Zongyang (2015)
With the popularity of Web 2.0, more and more users express and share opinions through various online platforms. Example platforms include news websites that support user commenting like Yahoo! News, social network sites that allow users to post messages like Facebook and Twitter, and community-based question answering sites which let users ask and answer questions. As the result, a huge amount of User Generated Content (UGC) is accumulated online in the forms of comments, tweets, question and answer posts, and others.